2019
DOI: 10.3390/cells8050413
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential (TRP) Channels in Health and Disease

Abstract: Almost 25 years ago, the first mammalian transient receptor potential (TRP) channel, now named TRPC1, was cloned and published (reviewed in [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 31 publications
0
21
0
1
Order By: Relevance
“…In addition, TRPC1 appears to contribute to the regulation of the epithelial-mesenchymal transition (EMT) in cancer; its inhibition suppresses TGF-β1-induced EMT 96,97 . TRPC3 is expressed in various immune cells and has been proposed to contribute to vascular inflammation [98][99][100] . Also, the brain-derived neurotrophic factor (BNDF) has the effect of upregulating TRPC3 in the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TRPC1 appears to contribute to the regulation of the epithelial-mesenchymal transition (EMT) in cancer; its inhibition suppresses TGF-β1-induced EMT 96,97 . TRPC3 is expressed in various immune cells and has been proposed to contribute to vascular inflammation [98][99][100] . Also, the brain-derived neurotrophic factor (BNDF) has the effect of upregulating TRPC3 in the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Transient receptor potential (TRP) channels are known to be involved in the regulation of cell migration, adhesion, and proliferation, as well as neoangiogenesis [56]. The TRP superfamily consists of the following six subfamilies, which are based on sequence homology: ankyrin-rich (TRPA1), vanilloid (TRPV1-6), canonical (TRPC1-7), melastatin-like (TRPM1-8), polycystin (TRPP2/3/5), and mucolipin (TRPML1-3) [57].…”
Section: Transient Receptor Potential (Trp) Channels and Endometriosismentioning
confidence: 99%
“…The TRP superfamily consists of the following six subfamilies, which are based on sequence homology: ankyrin-rich (TRPA1), vanilloid (TRPV1-6), canonical (TRPC1-7), melastatin-like (TRPM1-8), polycystin (TRPP2/3/5), and mucolipin (TRPML1-3) [57]. Their localization is ubiquitary, and they can be activated by a wide number of molecules and stimuli [56,58,59]. In endometrial biopsies, TRP expression levels have been reported to be differently down-and upregulated during the different phases of the menstrual cycle [60].…”
Section: Transient Receptor Potential (Trp) Channels and Endometriosismentioning
confidence: 99%
“…TRP channels have a broad distribution profile and are non-selective cation channels, with some of them being permeable for calcium. The superfamily of TRP channels consists of 28 members in humans, which are organized in six subgroups: TRPA, with A for "ankyrin"; TRPC, with C for "canonical", TRPM, with M for "melastatin", TRPML, with ML for "mucolipidin", TRPP, with P for "polycystin" and TRPV, with V for "vanilloid" [87].…”
Section: Trp Channelsmentioning
confidence: 99%